Kebermanfaatan Bantuan Dana Zis Produktif pada Mustahiq di UPZ Baznas Kecamatan Tegalsari Kabupaten Banyuwangi - Lely Ana Ferawati Ekaningsih (Koordinatorat Perguruan Tinggi Keagamaan Islam Swasta Wilayah IV Surabaya, 2017)
This study aims to determine the collection, distribution, empowerment of zakat funds, infaq, and shodaqoh are productive, and to know the usefulness of income and profit mustahiq recipient of productive funds. The type of this research is descriptive qualitative research, by using statistical procentase method to analyze the usefulness of ZIS earning fund at income and profit mustahiq. The results show that the ZIS productive fund assistance program in 2015 is a program of providing business capital assistance with the method of grant or qardhul hasan. In addition, the provision of ZIS earning funds is very beneficial for the improvement of mustahiq economy both in terms of revenue and in terms of profit.Keywords: Benefit, Productive Fund, Zakat, Infaq, Shodaqoh